Doppler Parameters of Uterine Arteries in the Evaluation of Placenta Accreta in Patients with Placenta Previa - Zheng L; Kong H; Wang F; Su Y; Chang Y; Xin H (International Journal of Women's Health, 2025)
Lili Zheng, Hongfang Kong, Fang Wang, Yuan Su, Yaqing Chang, Hong Xin Department of Obstetrics, The Second Hospital of Hebei Medical University, Shijiazhuang, Hebei, People’s Republic of ChinaCorrespondence: Hong Xin, Department of Obstetrics, The Second Hospital of Hebei Medical University, No. 215 Heping Xi Road, Shijiazhuang, Hebei, 050000, People’s Republic of China, Email 26200614@hebmu.edu.cnBackground: Placenta previa (PP) is an obstetric condition where the placenta is abnormally positioned in the lower uterine segment, potentially covering the cervical os. Placenta accreta (PA), often associated with PP, involves abnormal placental adherence to the myometrium, complicating delivery and increasing the likelihood of severe hemorrhage.Methods: This study retrospectively analyzed medical records of 167 patients diagnosed with PP from January 2018 to December 2022. Patients were divided into two groups based on the presence (n=113) or absence (n=54) of PA. Clinical parameters, including age, gestational weeks, BMI, obstetric history, and uterine artery blood flow parameters [peak systolic velocity (PSV), resistance index (RI), pulsatility index (PI)], were compared between the two groups. Statistical analysis involved independent samples t-tests, chi-square tests, and logistic regression to identify significant predictors of PA severity.Results: Significant differences were observed between the two groups in terms of gravidity, parity, abortions, cesarean sections, and uterine artery blood flow parameters. Patients with PA had higher gravidity, parity, abortion, and cesarean section rates, along with higher PSV and lower RI and PI values. Logistic regression identified PSV, RI, and PI as significant predictors of PA severity. ROC curve analysis confirmed the high predictive accuracy of these parameters, with AUC values indicating robust diagnostic performance.Conclusion: This study highlights the importance of detailed prenatal evaluation, particularly uterine artery blood flow parameters, in predicting and managing PA in PP patients.Keywords: placenta previa, placenta accreta, uterine artery blood flow, prenatal diagnosis